Diagnostic Findings and ERCP Treatment in Patients with Obstructive Jaundice during two years at H. Adam Malik Hospital, Medan - Gontar A. Siregar; Juwita Sembiring; Mabel Sihombing; Betthin Marpaung; Sri Sutadi; Abiran Nababan; Lukman Hakim Zain; Pengarapen Tarigan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Background: The methods of ERCP have been used for diagnostic and therapeutic purposes to pass bile fluid and extract stones from the bile duct in patients with obstructive extrahepatic jaundice. Method: A retrospective study was performed on patients with obstructive extrahepatic jaundice patients who underwent ERCP during a two-years time period from January 1999 to December 2000. ERCP was performed with a premedication of 10 mg midazolam, followed by a chollangiography contrast containing 1 mg/dl of Garamicin and 25 mg of Pethidine if sphincterotomy was performed. Results: From 126 patients with obstructive extrahepatic jaundice treated with ERCP, the male to female ratio was 1.86:1. The majority of the (group) of patients were between 51-60 years of age (33.3 % ). The youngest patient (group) was 24 years and the oldest 97 years. The diagnostic study found the following cases: normal 3 cases (2.8%), bile duct stone 46 cases (43.4%), carcinoma of ampula vater 20 cases (18.9%), CBD tumor 7 cases (6.6%), carcinoma of head of pancreas 2 cases (1.9%), diverticle 4 cases (3.8%), duodenal tumor 1 case (0.9%), carcinoma of ampula vater and bile duct stone 1 case (0.9%), SOD 5 cases (4.7%), CBD stricture 1 case (0.9%) and failure 16 cases (15.1%). The patients receivied the following treatment: sphyncterotomy 36 cases (51.4%), stent application 11 cases ( 15.7%), sphincterotomy with stent 18 cases (25.7%) and basket method 5 cases (7.1%). Keywords: ERCP, obstructive jaundice